The new Euromarkets : a theoretical and practical study of international financing in the eurobond, eurocurrency, and related financial markets - Scott-Quinn, Brian (New York : Wiley, 1975)
This book is a useful practical guide to practical procedures and some main trends in the international bond markets and the longer end of the Euro- currency markets. Eurocurrency markets are substitutes on both the borrowing and lending sides. For these reasons analysis of the Eurocurrency market is restricted to a consideration of its roles as an alternative source of medium/long-term funds and as an alternative investment medium to the Eurobond and foreign bond markets.
"A Halsted Press book."
Includes index.
Bibliography: p. [269]-271.
usc 23/05/18
Loans
Keywords: Euro-bond market; Euro-dollar market; Banks and banking; Banks and banking, International; Europe